Customary Marriage and Child Protection in Islamic Family Law: A Comparative Study of Indonesia and South Africa - Yenny Febrianty; Roni Jayawinangun; Jonathan Rey Cusa; Rindiana Larasati; Asmida Ahmad (UIN Sunan Gunung Djati Bandung, 2026)
Customary marriage functions as a social institution under numerous legal systems; yet, its implementation often poses significant obstacles to the safeguarding of children's rights, especially when performed without official registration or involving minors. This paper investigates the normative boundaries of customary marriage within the context of Islamic family law, emphasizing child protection via a comparative examination of Indonesia and South Africa. This study uses normative legal research methods—integrating legislative, conceptual, and comparative approaches—to analyse customary marital patterns, child protection norms, and judicial reactions in both countries. The findings indicate that Islamic family law acknowledges custom (‘urf) only under the condition that it aligns with the objectives of Sharīʿah (maqāṣid al-sharīʿah), specifically the safeguarding of progeny (ḥifẓ al-nasl), the mitigation of harm (dar’ al-mafāsid), and the attainment of justice (‘adl). The prevalence of unregistered traditional marriages and lenient marriage dispensation norms in Indonesia compromises children's legal identification, parental responsibility, and access to civil rights. Conversely, South Africa enforces more stringent normative regulations via compulsory registration and judicial measures to amend customary behaviors detrimental to children. This paper normatively asserts that child safety is an essential requirement for the legality of customary marriage and illustrates how Islamic family law serves as an internal corrective mechanism within diverse legal systems.